Immune system-dependent and -independent replication of the scrapie agent. - Lasmézas, C I (1996)
Using the severe combined immunodeficiency (SCID) mouse model, we investigated the requirement of the immune system for the development of scrapie after peripheral inoculation. A total of 33% of SCID mice, all but one immunologically reconstituted SCID mice (93%), and all CB17 control mice developed the disease. PrPres was detectable in the brains of all diseased animals and in the spleens of reconstituted SCID and CB17 control mice but not of the diseased non-immunologically reconstituted SCID mice. The immune system appears to be a primary target in the pathogenesis of scrapie, but direct spread to the central nervous system from the peritoneum via visceral nerve fibers can probably also occur.